The Next Generation of Research in Interpreter Education : Pursuing Evidence-Based Practices - Winston, Elizabeth A.; Roy, Cynthia B., 1950- (Book collections on Project MUSE., 2018)
"Volume builds on two traditions in education and research - long standing traditions in general and traditions that have taken root and continue to spread through our field of interpreter preparation"--